Genotypic diagnosis of familial Mediterranean fever (FMF) using new microsatellite markers: example of two extensive non-Ashkenazi Jewish pedigrees. Issue 5 (May 1997) - Dupont, M; Dross, C; Smaoui, N; Nedelec, B; Grateau, G; Clépet, C; Gourdier, I; Koné-Paut, I; Delpech, M; Demaille, J; Touitou, I
Abstract : Familial Mediterranean fever is an autosomal recessive disease characterised by multiple attacks of serosal inflammation in the absence of treatment. In the absence of timely diagnosis, renal amyloidosis is a life threatening complication. The diagnosis is often missed because no specific test is available. Early colchicine treatment prevents attacks and renal complications. The FMF gene (MEF) has been mapped to chromosome 16p 13.3 but has not yet been identified. We compared the suitability of a series of microsatellite markers (four of them were new) and propose the routine use of seven of these markers, exhibiting alleles in strong linkage disequilibrium with the disease and informative in 100% of diagnosed patients. Moreover, the discovery of a homozygous status for the 3-3-9 (or 3-3-18) haplotype at the core loci (D16S3070, D16S3082, and D16S3275), which was found in 73% non-Ashkenazi Jewish patients, points to a diagnosis of FMF, even in sporadic cases, with a risk of error of only 2.10(-5). Two extensive pedigrees covering most indications for genetic counselling are presented, showing that it is now possible both prospectively and retrospectively to identify members likely to have MEF mutations. With the help of this accurate test, colchicine treatment can be better targeted, especially where the symptomatology is mild or atypical.